2013
DOI: 10.1103/physrevlett.110.032501
|View full text |Cite
|
Sign up to set email alerts
|

Search for Superscreening Effects in a Superconductor

Abstract: The decay of19 O(β − ) and 19 Ne(β + ) implanted in niobium in its superconducting and metallic phase was measured using purified radioactive beams produced by the SPIRAL/GANIL facility. Half-lives and branching ratios measured in the two phases are consistent within one-sigma error bar. This measurement casts strong doubts on the predicted strong electron screening in superconductor, the so-called superscreening. The measured difference in screening potential energy is 110 (90) The cloud of electrons surroun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…Our final estimation of the half-life of 19 Ne, T 1/2 = 17.2569 ± 0.0019 (stat) ± 0.0009 (syst) s, is found in perfect agreement with the former measurements of Triamback et al [11] and Ujic et al [4], as illustrated in figure 14. However, it differs by 3.2 standard deviations from the value obtained by Broussard et al [12] and tends to discard the latter.…”
Section: Event By Event Compensation and Final Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our final estimation of the half-life of 19 Ne, T 1/2 = 17.2569 ± 0.0019 (stat) ± 0.0009 (syst) s, is found in perfect agreement with the former measurements of Triamback et al [11] and Ujic et al [4], as illustrated in figure 14. However, it differs by 3.2 standard deviations from the value obtained by Broussard et al [12] and tends to discard the latter.…”
Section: Event By Event Compensation and Final Resultssupporting
confidence: 90%
“…Thanks to a real-time digital multiparametric acquisition system, the half-life of 19 Ne has been measured with the unprecedented relative precision of 1.2 × 10 −4 . The result, in agreement with the measurements of Triambak et al and Ujic et al [4,11], is not consistent with the last measurement by Broussard et al [12]. The detailed analysis of the data provided by the multiparametric acquisition system has shown that at this level of precision, pile-up, baseline variations and primarily gain variations have to be considered carefully.…”
Section: Discussionsupporting
confidence: 37%
See 3 more Smart Citations